Exploring The Relationship Between Work Environment, Organizational Commitment, and Job Satisfaction, In the Formation of Organizational Citizenship Behavior - Ardani, Rahma Noviana (Universitas Muhammadiyah Pontianak, 2026)
This study examines the relationship between work environment, organizational commitment, and job satisfaction in shaping organizational citizenship behavior among employees of Café Kopi Kampung Ambarukmo. Using a quantitative approach, data were collected through Likert-scale questionnaires from 50 employees and analyzed using multiple linear regression after passing classical assumption tests. The results show that work environment and organizational commitment do not significantly affect organizational citizenship behavior, while job satisfaction has a positive and significant effect. These findings indicate that improving job satisfaction is essential to strengthening employees’ voluntary behavior, supported by a conducive work environment and stronger employee loyalty. Keywords: Work Environment; Organizational Commitment; Job Satisfaction; Organizational Citizenship Behavior